Implementasi Peran Efektifitas Komunikasi Orgnanisasi, Pelaksanaan K3 (Kesehatan dan Keselamatan Kerja) dan Budaya Perusahaan terhadap Motivasi Kerja Karyawan - Muntik Nur Hanifah; Rauly Sijabat; M. Fadjar Dharmaputra (Journal Economic Excellence Ibnu Sina, 2023)
This research aims to understand the implementation of the role of organizational communication effectiveness, implementation of K3 (work health and safety) and company culture on employee work motivation. The research method in this research is a quantitative research method. The population in this study were all permanent employees of PT Kebon Agung Trangkil Pati Sugar Factory, while the sample in this study was 100 respondents. Determining the sample size used a non-probability sampling technique because the population was relatively small, so the technique taken was saturated sampling (census). Data analysis in this study used the SPSS version 24 program. The data analysis technique used was the Multiple Linear Regression Analysis equation model. The results of the analysis and discussion show that there is no influence between the role of organizational communication variables (X1) on employee work motivation variables, There is an influence between the role of occupational health and safety variables (X2) on employee work motivation variables, There is an influence between corporate culture variables (X3) on employee work motivation variables, Variables The influence of the role of organizational communication, work health and safety and company culture simultaneously have a positive and significant effect on employee work motivation at PT Kebon Agung Sugar Factory Unit Trangkil Pati.